Morbimortality profile of nursing professionals due to COVID-19 in Brazil between the years of 2020 and 2022 - Amanda Gabrielle Carvalho Costa (2024)
Introduction: The global repercussion of the COVID-19 pandemic raises the need to understand the impact of the disease among nursing professionals, as they were responsible for direct care of infected people. Objective: To describe the morbimortality profile of nursing professionals due to COVID-19 in Brazil between 2020 and 2022. Methodology: An epidemiological study conducted with data collected at the Nursing Observatory of the Federal Council of Nursing. The data were tabulated using version 21 of the SPSS software and analyzed by descriptive analysis, using frequencies. Results: During the period analyzed, 64 610 cases of COVID-19 were reported among Nursing professionals in Brazil. Of these, 36 425 (56.4 %) were confirmed and 833 died, representing a case fatality rate of 2.29 %. In terms of cases, COVID-19 was prevalent among women (84.24 %) aged between 31 and 40 (41.34 %) years, residing in the southeastern part of the country (29.77%) and infected in 2020 (66.79 %). As for deaths, the prevalence of cases occurred in 2020 (52.10 %) among women aged 41 to 50 years (68.07 %), residing in the northern region of Brazil (28.93 %). Nursing professionals had a 14 % higher mortality rate than the general population of Brazil, with a higher frequency among men. Conclusion: The study raises the need to build public policies aimed at protecting these workers. Such policies must seek to guarantee better working conditions, ongoing education, and to address gender inequalities.